PAX Scientific - Isaacs, Andrew M., (SAGE Knowledge. Cases., 2017)
The PAX Scientific case study is a technology startup case that allows students to discuss how a science-driven invention, theory, or idea can be launched into the commercial marketplace. One of the key issues facing leadership is whether to continue to pursue a licensing strategy for its products versus manufacturing those products and selling them themselves. The case allows students to think through how the company can grow beyond a small family business to a much larger company with much greater revenue and profitability potential.